Expendable to Essential: Conceptualizing the Rhetorical Othering of Frontline Workers - Sarah Sexton (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2025)
As my article discusses, Over the course of the pandemic, there has been a social shift in the way certain workers are represented within American society. Everyday workers such as grocery store clerks, baristas, and retail managers were deemed “essential workers” as COVID-19 created a global healthcare crisis. Although these workers were declared as essential to the wellbeing of American society during the pandemic, there is evident dissent between the collective experience of frontline employees and those outside of this community. The rhetoric produced by members of the essential community, including myself, alongside statistical findings reflect an ongoing instance of socioeconomic “othering” against this community due to their racial and/or economic position within American society. This is characteristic of a capitalistic society that is simultaneously exploitative and reliant upon the services of those who are disadvantaged and marginalized upon the basis of their socioeconomic status. Analyzing the rhetorical dissent between members of the essential community and other classes of American society illustrates this concept of othering and the ongoing systematic oppression that continues to exploit workers.
Keywords: essential; COVID-19; rhetorical appeals; race; socioeconomic divisions; pandemic